(3TQM fgL GdHdGZIs - (3bhGe GdOjf jhSa Hf MSf GdMSjfj GdTjQGRi GdMfajs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3eMeO Hf adGM GdSYOi GdcGXei s)
(3ChdgG (B:s
(3GeG HYO aGfc eef GSJXgQ Hg Ydi GbGeI GdOjf aGbeY Hg fNhI GdGKje s
(3BNQgG (B:s
(3hNQL Edi Mfjf eY GdHi hgh Ydi TQcg MJi GSde HGdLYQGfIhGdMeO ddg s
(3fSNI KGefIs
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs